STUDI KASUS TENTANG SISWA YANG BERPERILAKU AGRESIF PADA KELAS X SMA SANTUN UNTAN PONTIANAK - Amalia, Alisha; Astuti, Indri; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis is entitled "Case Study About Aggressive Behavior in High School Students of SMA Santun Untan Pontianak". The purpose of this study is to obtain an objective picture of case studies on aggressive behavior in grade X students SMA Santun Untan Pontianak. The approach used in this research is qualitative by using descriptive method. This form of research is a case study. Data collection techniques used are direct observation, direct communication, and home visit (home visit). The results of research subjects who behave aggressively are physical aggressive behavior that is making dangerous physical contact, and verbal aggressive behavior is to say harshly. The alternative assistance provided is by using the REBT counseling approach with cognitive dispute techniques and behavioral dispute. Based on the above conclusions, the suggestion for the case subjects to keep running the alternative assistance that has been given. And keep trying to maintain the positive changes by not joking by making dangerous physical contacts and establish good communication, polite, and more appreciate the feelings of others.Keywords: Case Study, Aggressive BehaviorÂ Â